Tindak Tutur Memuji dalam Film Kaze Tachinu - Nimatul Maulida (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2019)
This study aims to describe the use of Japanese compliment expression in Kaze Tachinu's movie. It includes the types of compliment, the forms of expression and the categories of compliment topics. The data of this study were taken from the utterances of characters which contain compliment expressions. The type of compliment expression, which are bound and unbound compliments, were then analyzed based on Yuan's theory. The forms of compliment expressions were analyzed based on the theories of Huang and Tseng, and the topic of compliment was analyzed by using Holmes's theory. This type of research is descriptive qualitative research with a pragmatic approach. The results of the study found 2 types of unbound compliments, they were direct and indirect compliment, each of which got 4 topics. And then for the bound compliment , there were found 13 expressive of compliments that consist of realization to complimenting directly and complimenting indirectly. Expressive forms of compliment in indirect compliment were found to be 11 forms, they are surprise, explanation, evaluation, knowing, offering reward, contrast, assumption, admiration, appreciation, request and pleasing. Direct compliment are very varied with the existence of evaluative markers, which are vocabulary that has the same meaning.Â